Budaya masyarakat dalam membangun rumah vernakular di Pesisir Pantai - Wilhelmus Hary Susilo (Faculty of Social and Political Science, Universitas Airlangga, 2014)
Indonesia is a country with various cultural heritages, amongst of them is the way people construct their house. Understanding culture of society in buliding house will enable people to maintain tradition and distinctness of each region. The purpose of this research is to describe the way people build houses typical to west coast area in Sumatra. Method uses in this research include (1) preparatory team, (2) assessment reference of vernacular house, (3) preliminary survey, (4) field observation, (5) interview, (6) measurement: to be proceed manually by the use of a measuring manual; conducted towards an architecture object, (7) micro study documentation. The data analysis covered six activities: (1) documenting the results of open-ended interviews; (2) portrayal of the measurement results; (3) aspect analysis: scatter pattern, building pattern, details of architecture, materials and structural proportions; (4) findings of unique elements building; (5) comparation to concept of new vernacular architecture; (6) finding the potential for vernacular architecture parts of the coastal part of Indonesia. Finally a new vernacular model house architecture can be obtained as a dynamic model used by people in building their houses.